2013
DOI: 10.26719/2013.19.6.547
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of pharmacists and health-care workers regarding oral contraceptives correct usage, side-effects and contraindications

Abstract: Despite the success of the Iranian family planning programme, the number of unwanted pregnancies remains high. To investigate whether health workers in Tabriz are providing correct information and counselling about OCP use, the current study was planned to examine the level of knowledge, attitude and practice of OCP providers. A sample of 150 health-care workers in health houses and 150 community/hospital pharmacists answered a questionnaire about knowledge of correct use of OCP, side-effects, contraindication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
6
5
0
Order By: Relevance
“…Moreover, another study carried out in Iran using a questionnaire about OCPs use showed that the knowledge of pharmacists about OCPs was not at the expected level, and in some areas they provided incorrect information. Deficiencies in communication skills also were apparent 32. The last two mentioned studies undertaken in Iran confirmed the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, another study carried out in Iran using a questionnaire about OCPs use showed that the knowledge of pharmacists about OCPs was not at the expected level, and in some areas they provided incorrect information. Deficiencies in communication skills also were apparent 32. The last two mentioned studies undertaken in Iran confirmed the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar percentages were reported by a study conducted among pharmacists in Egypt [17]. Other studies had shown that respondent knew how to handle one missed pill but few knew how to handle multiple missed pills [5,14]. This indicates a gap in dispensing practices that can affect OCPs users' adherence [10,11].…”
Section: Discussionsupporting
confidence: 71%
“…Placebo-controlled trials had failed to show any association between low-dose combined OCs and weight gain [8]. Similar percentages were reported among pharmacists (76.7 %) by another study [14].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The study findings have revealed that pharmacists and pharmacy trainees showed good knowledge about OCPs, who were aware of the non-contraceptive uses and the most common side effects of OCPs. Similar to these results, an Iranian study showed that more than 90% of pharmacists have identified the non-contraception use of OCPs and their side effects [ 22 ]. Also, a study in the United Arab Emirates showed that the majority of pharmacists could identify the most common side effects of OCPs, such as weight gain and mood fluctuations [ 23 ].…”
Section: Discussionsupporting
confidence: 58%